Analisis Pengelolaan Limbah Home Industry Mebel Di Desa Watupasang Kedamean Dalam Perspektif Hukum Lingkungan - Euis Rike Pramadhanti; Nur Qoilum (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study aims to analyze the implementation of environmental law in waste management practices of furniture home industries in Watupasang Village, Kedamean District, Gresik Regency, and to identify the level of compliance and obstacles faced by business actors in fulfilling waste management obligations. This research uses an empirical juridical method with statutory and sociological approaches. Data were collected through observation, interviews, and literature studies. The results show that waste management practices are still carried out conventionally and have not fully complied with Law Number 32 of 2009 concerning Environmental Protection and Management and Government Regulation Number 22 of 2021. Wood waste is generally burned openly without emission control, while liquid waste from chemicals such as paint and thinner is not processed according to environmental standards. Low compliance is influenced by limited capital, lack of legal awareness and environmental understanding, weak government supervision, and limited access to environmentally friendly waste management technology. Therefore, legal education, stricter supervision, and adequate waste management facilities are needed to create sustainable and environmentally sound waste management.